IDENTIFYING HEALTH RISKS OF EXCESSIVEUSE OF SMARTPHONES IN ADOLESCENTS - Tufail, Muhammad Mutasim Billah; Shakeel, Muhammad; Farooqui, Raheel (The journal of contemporary issues in business and government, 2022)
It is less likely to be known about risk perception amongst parents who have their adolescents stay in front of smartphones. Our objective is to analyze the usage of smartphones among the young generation nowadays and identify health-related risks linked to them. The smartphone market is the biggest in the world; this cool thing is creating open-mindedness for the whole world and negatively impacting adolescents' minds. This new era's generation is rapidly converting into severe phobias, depressions, and neck-shoulder pain, which are not a good sign. Fifteen students' parents surveyed a private school Students aged between 15 to 17. The result shows that 70% of the students arephone addicted to the problem of anxiety, weak eyes, and carelessness.